The Development of Equipment and Models of Sport Training for Early Childhood Education Program: - Imam Sujoko; Juriya; Sefria Indah Primasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The purpose of this research is to improve the sports development system in early childhood education through the infrastructure approach and training model applied to early childhood. The specific goal to be achieved is to create training models along with supporting facilities and infrastructure that can be used in the development of sports at an early age that are able to overcome limited funds and space, as well as provide safety, comfort and encourage children's desire to move in supporting their multilateral skills. It is hoped that the products and training models from this research will obtain Intellectual Property Rights so that they can be used nationally. This research is research and development (Research and Development) with research subjects from kindergarten to lower grades of elementary school (1-3). The stages of development are carried out by: 1) analyzing the information that has been collected, 2) planning the research, 3) developing the initial product, 4) expert validation and revision, 5) large-scale trials and revision of the final product. The research subjects were kindergarten and elementary school students in several schools in Metro City with a total of 100 students. Data were collected by observation using observation sheets and open questionnaires, interviews with material and media experts, teachers and audio-video recording studies in the field. The data obtained were analyzed in stages: 1) data reduction, 2) data classification, 3) data display, 4) data interpretation.